The Impact of Prenatal Exposure to Bisphenol A on Male Reproductive Function - Hart, Roger J. (Frontiers in Endocrinology, 2020)
Bisphenol A (BPA) is a recognised xenoestrogen, in that it possesses oestrogenic and anti-androgenic properties. These endocrine-disrupting effects of BPA at the oestrogen receptor (ER) occur at very low concentrationsdespite the very low affinity of BPA for the ERβ, which is 10,000 times lower than that of 17-β oestradiol, and despite the European regulatory authorities stating that BPA is safe, at usual exposure concentrations, the use of BPA in baby drink bottles was banned in 2011. There exists conflicting evidence from human epidemiological studies as to its influence on adult male reproductive function, although animal data is more convincing. This mini-review will report on the limited epidemiological data from human studies relating early life exposure to BPA on adult male reproductive function. A long term follow-up study from Western Australia using a birth cohort, the Raine Study, demonstrated no adverse associations of antenatal exposure to BPA exposure, and potentially a positive association with antenatal BPA exposure with sperm concentration and motility at 20 years of age, although recent scientific reports suggest traditional measures of BPA exposure may underestimate exposure levels, which makes data interpretation potentially flawed.